A Motion Vector Sensor via Direct‐Current Triboelectric Nanogenerator. (2nd July 2020) - Yin, Xing; Liu, Di; Zhou, Linglin; Li, Xinyuan; Xu, Guoqiang; Liu, Lu; Li, Shaoxin; Zhang, Chuguo; Wang, Jie; Wang, Zhong Lin
Abstract: Motion vector sensors play an important role in artificial intelligence and internet of things. Here, a triboelectric vector sensor (TVS) based on a direct‐current triboelectric nanogenerator is reported, for self‐powered measuring various motion parameters, including displacement, velocity, acceleration, angular, and angular velocity. Based on the working mechanism of the contact‐electrification effect and electrostatic breakdown, a continuous DC signal can be collected to directly monitor moving objects free from environmental electromagnetic signal interference existing in conventional self‐powered TVSs with an alternative‐current signal output, which not only enhances the sensitivity of sensors, but also provides a simple solution to miniaturize the sensors. Its sensitivity is demonstrated to be equivalent to state‐of‐the‐art photoelectric technology by a comparative experiment in an intelligent mouse. Notably, an intelligent pen based on the miniaturized TVS is designed to realize motion trajectory tracing, mapping, and writing on the curved surface. This work provides a new paradigm shift to design motion vector sensors and self‐powered sensors in artificial intelligent and internet of things. Abstract : The motion vector sensor is designed to monitor variable motion parameters including displacement, velocity, acceleration, angular, and angular velocity. Multifunction motion trajectory tracing, mapping, and writing on the curved surface are also realized through an intelligent pen based on the miniaturized vector sensor.